Waqf demystified: a guide to key terms and concepts / Rohayati Hussin, Nur Irinah Mohamad Sirat and Nurul Mazrah Manshor - Hussin, Rohayati; Mohd Sirat, Nur Irinah; Manshor, Nurul Mazrah (Universiti Teknologi MARA, Kedah, 2024)
Waqf is an Arabic Masdar that originates from the verb waqafa, signifying "restraint," "prevention," and "detention." Waqf is private ownership of assets with restrictions on sale, inheritance, grant, and will. The assets' original source is unaffected by these restrictions. The Shafie, Hanbali, and Maliki schools adhere to four principles of waqf, which are as follows: (1) sighah, (2) waqif, (3) mauquf 'alaih, and (4) mawquf. In regard to the Hanafi school of thought, it is noteworthy that they recognize a single pillar, specifically the sighah. While Muslim jurists throughout history have held differing views on the specific laws governing a genuine waqf, there exists a consensus on the legal requirements or regulations that must be adhered to in order to create a waqf. Some academics include "mutawalli" in the frequently employed terms for the management waqf.